DIGITAL TRANSFORMATION OF PUBLIC ADMINISTRATION: PROACTIVE CUSTOMER SUPPORT (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
The article considers the issue of digital transformation, which can become the basis forthe further development of the principle of management by results of the state, since it allows you toovercome its previously identified limitations. The purpose of this article is a detailed study of new businessmodels, including the so-called proactive service based on data, as well as the integration of modernfragmented information systems and communication channels. It is shown that despite the resultsachieved, problems associated with an insufficient level of openness, customer orientation and activityremain relevant. For example, government agencies are reluctant to disclose information that can beused to create added value in the form of relevant and relevant open data. The e-government developmentindex (EGDI) in the Republic of Kazakhstan is analyzed. The results of the analysis revealed a highlevel of development of e-government. However, according to the authors, it is necessary to study inmore detail new business models, including the so-called proactive service based on data, as well asthe integration of modern fragmented information systems and communication channels to implementa multi-channel service model by creating a single “front office” aimed at providing the availability ofinformation and services at anytime, anywhere and on any device (contact center, web portal, smartmessengers, mobile applications, SMS messages).